2016
DOI: 10.1097/j.pain.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

A possible neural mechanism for photosensitivity in chronic pain

Abstract: Patients with functional pain disorders often complain of generalized sensory hypersensitivity, finding sounds, smells, or even everyday light aversive. The neural basis for this aversion is unknown, but cannot be attributed to a general increase in cortical sensory processing. Here we quantified the threshold for aversion to light in patients with fibromyalgia, a pain disorder thought to reflect dysregulation of brain pain-modulating systems. These individuals expressed discomfort at light levels substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 65 publications
2
45
1
Order By: Relevance
“…Finally, a retrograde labeling of the PAG demonstrated glutamate-like immunoreactivity in several regions of the brain including the occipital cortices [4], further supporting a link between the visual system and pain response. Martenson and colleagues [51] have recently identified a possible circuitry for photic stimulation that included pain modulating “ON-cells” and “OFF-cells” in the RVM which project to the dorsal horn of the spinal cord where they are postulated to modulate somatosensory processing. An imbalance of these may lead to enhanced or diminished pain with ON-cells facilitating nociception and OFF-cells inhibiting nociception.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a retrograde labeling of the PAG demonstrated glutamate-like immunoreactivity in several regions of the brain including the occipital cortices [4], further supporting a link between the visual system and pain response. Martenson and colleagues [51] have recently identified a possible circuitry for photic stimulation that included pain modulating “ON-cells” and “OFF-cells” in the RVM which project to the dorsal horn of the spinal cord where they are postulated to modulate somatosensory processing. An imbalance of these may lead to enhanced or diminished pain with ON-cells facilitating nociception and OFF-cells inhibiting nociception.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that off-cells in the RVM that are associated with descending inhibitory analgesic pathways receive inputs from glutamatergic vlPAG projection neurons [33; 42; 59]. Numerous studies show a shift in homeostatic balance from descending inhibitory drive to descending facilitatory drive in the RVM that may contribute importantly to chronic pain states [9; 12; 25; 35; 40; 41; 55; 64; 68]. It is unclear whether this shift to descending facilitatory drive also occurs in the PAG, or involves upstream projections from the RVM.…”
Section: Discussionmentioning
confidence: 99%
“…A number of cell parameters, defined as previously described, 1,11,50 were used to characterize reflex-related changes in RVM cell activity. In experiments testing heat-evoked withdrawals, we analyzed the number of spikes per ON-cell burst, the latency from burst onset to hindpaw withdrawal, and the peak firing rate during the burst.…”
Section: Methodsmentioning
confidence: 99%